Structural and cyclical risks in housing markets in OECD countries - Tobias Just; Hannah Salzberger (Intereconomics, 2024)
This paper analyses the housing markets of OECD countries using a scoring model. This model is based on a European Systematic Risk Board approach to risk assessment of housing markets but extends this approach in two important ways. First, this paper distinguishes between cyclical and structural risk factors. Markets facing higher susceptibility to cyclical risks necessitate a distinct policy approach to prevent or handle disruptions, as opposed to markets primarily affected by structural risks. Second, it illustrates that scoring models contain subjective aspects, e.g. in the choice of weighting factors. We develop four distinct models to weigh risk factors. We show that these different weighing schemes have a significant impact on the estimated risk scores. For policy decisions, such models can therefore only be an indication of the vulnerability of housing markets to crises. Therefore, several scenarios and models should be calculated in parallel to reduce subjectivity.
Keywords: R31; E30; 330; Housing market; Scoring model; OECD countries; Wohnungsmarkt; Scoring-Modell; OECD-Staaten